Clinical manual of otolaryngology (head and neck surgery) - Davidson, Terence M.; Husseman, Jacob (Jaypee Brothers Medical Publishers (P) Ltd., 2013)
Beginning with an introduction, history and physical examination, the following chapters describe common conditions in different parts of the head and neck, the ear, the nose, the throat, and the neck. Chapters on facial plastic and reconstructive surgery, psychosocial considerations, sleep medicine, and HIV/AIDS and Hepatitis, are also included. Authored by recognised specialists from the University of California School of Medicine, San Diego, this clinical manual includes more than 200 colour images and illustrations, as well as case studies on cosmetic surgery and maxillofacial trauma. Key Points: Clinical manual discussing key diseases of the head and neck. Examines numerous different conditions affecting the ear, nose, throat and neck. Includes chapter on facial plastic and reconstructive surgery with case studies.